A Critical Analysis of The Movie Kartini About Feminism Directed by Hanung Bramantyo - Tania Priscila; Wikanengsih (IKIP Siliwangi, 2024)
Kartini is an Indonesian emancipation and feminism figure. One of the movies we talk about is Kartini directed by Hanung Bramantyo and Dian Sastro as Kartini, is one of the most popular movies in Indonesia. It is a movie of the era of the